Spatiotemporal Evolution and Fluctuation Characteristics of a Centrifugal Compressor under Near-Stall Conditions and High Mass-Flow Rate - Kang Xiao; Zhengdao Wang; Hui Yang; Yikun Wei (Energies, 2022)
Spatiotemporal evolution and fluctuation characteristics of a centrifugal compressor are investigated by numerical simulation under near-stall conditions and with a high mass-flow rate. The large-eddy simulation (LES) for unsteady computations is implemented in the numerical simulation of unsteady flow. The internal flow physical mechanism of the centrifugal compressor is presented at a high mass-flow rate (1.1 Qn) and low mass-flow rate (0.8 Qn, near-stall). The spatiotemporal evolution of the velocity and streamline for the internal flow of the centrifugal compressor demonstrates that a lot of large-scale eddies near the tongue are transformed into small-scale ones at high mass-flow rates. High mass-flow rate resulted in excessive fluid velocity in the impeller. A large amount of impact loss massive backflow appears near the tip clearance, and boundary layer separation of the suction surface emerges firstly and at a low mass-flow rate. Considerable flow loss occurs in the centrifugal compressor at the two non-designed operating flow rates. Several pressure and velocity fluctuations in the key position of the compressor are presented by the two deviations from design conditions. The analysis of the fast Fourier transform (FFT) and amplitude spectrum show that the starting point of flow instability in the impeller is different for the two deviations from design-condition flow rates. Understanding the spatiotemporal evolution and spatiotemporal characteristics of pressure and velocity fluctuations can provide insight into the unsteady internal flow of centrifugal compressors at high mass-flow rates (1.1 Qn) and near-stall conditions (0.8 Qn).